Pregnancy outcomes in women with endometriosis and/or ART use: a population-based cohort study. Issue 10 (26th August 2022) - Ibiebele, Ibinabo; Nippita, Tanya; Baber, Rodney; Torvaldsen, Siranda
Abstract: STUDY QUESTION: What is the association between endometriosis and adverse pregnancy outcomes with ART use and non-use? SUMMARY ANSWER: Endometriosis and ART use are both associated with increased risk of preterm birth, antepartum haemorrhage, placenta praevia and planned birth (caesarean delivery or induction of labour). WHAT IS KNOWN ALREADY: There are contradictory findings on the association between endometriosis and adverse pregnancy outcomes, and many large studies have not considered the effect of ART use. STUDY DESIGN, SIZE, DURATION: Population-based cohort study of 578 221 eligible pregnancies during 2006–2015, comparing pregnancy outcomes across four groups (No endo/no ART, No endo/ART, Endo/no ART and Endo/ART). PARTICIPANTS/MATERIALS, SETTING, METHODS: All female residents of New South Wales, Australia aged 15–45 years and their index singleton pregnancy of at least 20 weeks gestation or 400 g birthweight. Linked hospital, pregnancy/birth and mortality data were used. Modified Poisson regression with robust error variances was used to estimate adjusted risk ratios (aRRs) and 99% CIs, adjusting for sociodemographic and pregnancy factors. MAIN RESULTS AND THE ROLE OF CHANCE: Compared to women without endometriosis who had pregnancies without ART use, there was increased risk of preterm birth (<37 weeks) in all groups [No endo/ART (aRR 1.85, 99% CI 1.46–2.34), Endo/no ART (aRR 1.24, 99% CI 1.06–1.44), Endo/ART (aRR 1.93, 99% CI 1.11–3.35)] and antepartum haemorrhage [No endo/ART (aRR 1.99, 99% CI 1.39–2.85), Endo/no ART (aRR 1.31, 99% CI 1.03–1.67), Endo/ART (aRR 2.69, 99% CI 1.30–5.56)] among pregnancies affected by endometriosis or ART use, separately and together. There was increased risk of placenta praevia [No endo/ART (aRR 2.26, 99% CI 1.42–3.60), Endo/no ART (aRR 1.66, 99% CI 1.18–2.33)] and planned birth [No endo/ART (aRR 1.08, 99% CI 1.03–1.14), Endo/no ART (aRR 1.11, 99% CI 1.07–1.14)] among pregnancies with endometriosis or ART use, separately. There was increased risk of placental abruption [No endo/ART (aRR 2.36, 99% CI 1.12–4.98)], maternal morbidity [No endo/ART (aRR 1.67, 99% CI 1.07–2.62)] and low birthweight (<2500 g) [No endo/ART (aRR 1.45, 99% CI 1.09–1.93)] among pregnancies with ART use without endometriosis. There was decreased risk of having a large-for-gestational age infant [Endo/no ART (aRR 0.83, 99% CI 0.73–0.94)] among pregnancies with endometriosis without ART use. LIMITATIONS, REASONS FOR CAUTION: Endometriosis is often under-diagnosed and women with a history of hospital diagnosis of endometriosis may represent those with more symptomatic or severe disease. If the effects of endometriosis on pregnancy are greater for those with more severe disease, our results may over-estimate the effect of endometriosis on adverse pregnancy outcomes at a population level. We were unable to assess the effect of endometriosis stage or typology on the study outcomes. WIDER IMPLICATIONS OF THE FINDINGS: These results suggest that women with endometriosis including those who used ART to achieve pregnancy are a higher-risk obstetric group requiring appropriate surveillance and management during their pregnancy. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Prevention Research Support Program, funded by the New South Wales Ministry of Health. The funder had no role in the design, data collection and analysis, interpretation of results, manuscript preparation or the decision to submit the manuscript for publication. The authors have no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.